'Offenbarung, Philosophie, und Theologie': Karl Barth and Georges Florovsky in dialogue. Issue 3 (7th July 2015) - Baker, Matthew
Abstract: Karl Barth and Georges Florovsky interacted in several contexts, beginning in 1931 and then later within the ecumenical movement. Although some have noted a 'Barthian' accent in Florovsky's Christocentric theology, in fact both theologians remained critical of the other. Making use of extensive historical sources, this article attempts to reconstruct the meeting between Barth and Florovsky, and to pinpoint the areas of fundamental reservation and disagreement between the two. As will be shown, at the heart of their disagreement lay the role of eschatology in its impact on ecclesiology, a difference finally Christological in foundation. This fundamental disagreement shows itself likewise in relation to the two theologians' ideas concerning history, the relationship of philosophy to theology and the place of Hellenism in Church tradition. The role of Florovsky's opposition to the sophiology of Bulgakov in his interpretation of Barth, and Florovsky's stance vis-à-vis the debate between Barth and Brunner on natural theology, will also be considered. Uniquely, Florovsky anticipated the contemporary debate concerning Barth's doctrine of election, and drew crucial connections between Barth and Bulgakov on this point – an issue which for him was related to the question of the role of German Idealism in modern theology. Notwithstanding these disagreements, this article concludes by highlighting crucial areas of convergence between Barth and Florovsky concerning Christocentrism, revelation and theology as an enterprise in fides quaerens intellectum. Florovsky's ideas on analogy, naming and realism in theology will also be illumined, in relation to Barth and with reference to Bulgakov and Torrance.